miRNA–mRNA–protein dysregulated network in COPD in women - Li, Chuan Xing; Gao, Jing; Sköld, C. Magnus; Wheelock, Åsa M. (Frontiers in Genetics, 2022)
Rationale: Chronic Obstructive Pulmonary Disease (COPD) is a complex disease caused by a multitude of underlying mechanisms, and molecular mechanistic modeling of COPD, especially at a multi-molecular level, is needed to facilitate the development of molecular diagnostic- and prognostic tools and efficacious treatments. Objectives: To investigate miRNA-mRNA-protein dysregulated network to facilitate prediction biomarkers and disease subnetwork in female COPD. Measurements and Results: Three omics data-blocks (mRNA, miRNA, protein) collected from BAL cells from female current smoker COPD patients, smoker with normal lung function, and healthy never-smokers were integrated with miRNA-mRNA-protein regulatory networks to construct a COPD-specific dysregulated network. Further downstream network topology, literature annotation and functional enrichment analysis identified both known and novel disease-related biomarkers and pathways. Both abnormal regulations in miRNA induced- mRNA transcription and protein translation repression play roles in COPD. Finally, the Let-7 – AIFM1 – FKBP1A pathway is highlighted in COPD progression. Conclusions: For the first time, a comprehensive miRNA-mRNA-protein dysregulated network of primary immune cells from the lung related to COPD in females was constructed to elucidate specific biomarkers and disease pathways. The multi-omics network provides new molecular insight from a multi-molecular aspect and highlights dysregulated interactions. The highlighted Let-7 – AIFM1 – FKBP1A pathway also indicate new hypotheses of COPD progression.